Is uplift of volcano clusters in the Tohoku Volcanic Arc, Japan, driven by magma accumulation in hot zones? A geodynamic modeling study. Issue 6 (28th June 2016) - George, Ophelia A.; Malservisi, Rocco; Govers, Rob; Connor, Charles B.; Connor, Laura J.
Abstract: In many volcanic arcs, the rate of tectonic uplift cannot be explained by lithospheric plate motion alone but may be associated with dynamic uplift. Buoyant forces associated with underplated magma bodies lift the upper crust and leads to relatively high rates of topographic change. One such region is northern Honshu, Japan, where Quaternary volcano clusters are spatially associated with uplifted crust and isostatic gravity anomalies. Axisymmetric inversion of Bouguer gravity data for the Sengan volcano cluster shows that these gravity anomalies can be modeled by 30 km radius bodies emplaced at ∼15 km depth. Axisymmetric, finite element models, generated using GTECTON, of a layered Earth representative of the Tohoku crust indicate that the deformation of these midcrustal intrusions produces elevated topography on the surface directly above the intrusion that is bounded by a shallow peripheral trough. The wavelengths of vertical deformation produced by these bodies are sensitive to the thickness of the models' elastic layer and relatively insensitive to the models' rheology. This suggests that the amplitude of the vertical deformation represents a trade‐off between the size of the intrusion and the thickness of the elastic layer and is less strongly influenced by the rheology of the lithosphere into which the bodies are emplaced. Our results are consistent with hot zone and hot finger models for the arc and indicate that Tohoku Volcanic Arc features such as gravity anomalies and uplifted basement are related to crustal magma intrusions and hot zones rather than directly related to mantle processes. Key Points: A middle to lower crust density anomaly coincides with the Sengan volcano cluster and is consistent with a hot zone magma intrusion model Axisymmetric numerical models confirm dynamic uplift of the crust across volcanic clusters